2012
DOI: 10.1158/1078-0432.ccr-11-2529
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors in the Treatment of Epidermal Growth Factor ReceptorMutant Non–Small Cell Lung Cancer Metastatic to the Brain

Abstract: Brain metastases are a common and devastating consequence of disease progression in patients with nonsmall cell lung cancer (NSCLC). The epidermal growth factor receptor (EGFR) inhibitors erlotinib and gefitinib have shown efficacy in patients with NSCLC and brain metastases. The cerebrospinal fluid (CSF) exposure to these drugs is a small fraction of the plasma levels achieved with standard doses, but disruption of the blood-brain barrier in the presence of central nervous system metastases is likely to lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 64 publications
2
91
1
2
Order By: Relevance
“…By limiting the analysis to prospective studies, there was no significant difference in intracranial disease control and survival outcomes between concurrent upfront WBRT plus TKIs and TKIs alone. Thus, considering the high intracranial ORR, consistent with results from other reviews (99)(100)(101), TKIs alone may be used upfront before WBRT in those pts with EGFR mutated NSCLC and asymptomatic BM. With a similar strategy the side effects of WBRT may be potentially avoided as long as intracranial disease is well controlled by TKIs alone.…”
Section: Standard Schedulessupporting
confidence: 80%
“…By limiting the analysis to prospective studies, there was no significant difference in intracranial disease control and survival outcomes between concurrent upfront WBRT plus TKIs and TKIs alone. Thus, considering the high intracranial ORR, consistent with results from other reviews (99)(100)(101), TKIs alone may be used upfront before WBRT in those pts with EGFR mutated NSCLC and asymptomatic BM. With a similar strategy the side effects of WBRT may be potentially avoided as long as intracranial disease is well controlled by TKIs alone.…”
Section: Standard Schedulessupporting
confidence: 80%
“…Pemetrexed, in combination with cisplatin, has recently been used in the treatment of metastatic NSCLC patients (9)(10)(11). NSCLC patients with the exon 19 deletion have a distinctive pattern of brain metastases which usually present as multiple small metastases with low levels of brain edema (12,13). Certain studies have indicated that gefitinib and erlotinib penetrate into the central nervous system and elicit responses in NSCLC patients with brain metastases (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC patients with the exon 19 deletion have a distinctive pattern of brain metastases which usually present as multiple small metastases with low levels of brain edema (12,13). Certain studies have indicated that gefitinib and erlotinib penetrate into the central nervous system and elicit responses in NSCLC patients with brain metastases (13)(14)(15). It was revealed that pemetrexed had a slightly higher brain penetration capability compared to that of methotrexate, by the analysis of arterial blood and frontal cortex microdialysis samples obtained simultaneously (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR tyrosine kinase inhibitors have weak central nervous system (CNS) penetrance (29)(30)(31), and strategies for pulsed high-dose therapy have been used to obtain CNS disease stability (32,33). Although patients with EGFRmutant tumors were not treated with concurrent tyrosine kinase inhibitors in our cohort, EGFR TKI therapy was initiated before gamma knife in approximately half of the EGFR-mutant patients, and we investigated whether this was a potential confounder for local control (Table 4).…”
Section: Tki Use In Egfr Kinase Domain-mutant Patientsmentioning
confidence: 99%